1998
DOI: 10.1046/j.1365-2141.1998.00996.x
|View full text |Cite
|
Sign up to set email alerts
|

Cryptic deletions and inversions of chromosome 21 in a phenotypically normal infant with transient abnormal myelopoiesis: a molecular cytogenetic study

Abstract: Summary.A case of transient abnormal myelopoiesis in a normal newborn without features of Down syndrome is described. The majority of bone marrow cells analysed belonged to a chromosomally abnormal clone with trisomy for chromosomes 18 and 21. Complex intrachromosomal rearrangements of one chromosome 21, demonstrated by fluorescence in situ hybridization using locus-specific probes, were found in a minor population of the clonal cells. These rearrangements involved loci previously shown to be rearranged in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 7 publications
(10 reference statements)
0
10
0
Order By: Relevance
“…FISH studies with probes covering different segments of the long arm of chromosome 21 showed that the marker chromosomes resulted from complex rearrangements, with uneven duplications of different regions of 21q. Cryptic complex chromosome 21 rearrangements, associated with deletions and inversions, have previously been reported in an infant with transient abnormal myelopoiesis (Kempski et al, 1998). Deletions of the distal part of one chromosome 21 including AML1 have been reported to occur in children with constitutional trisomy 21 and acute megakaryocytic leukemia (Kempski et al, 1997).…”
Section: Discussionmentioning
confidence: 98%
“…FISH studies with probes covering different segments of the long arm of chromosome 21 showed that the marker chromosomes resulted from complex rearrangements, with uneven duplications of different regions of 21q. Cryptic complex chromosome 21 rearrangements, associated with deletions and inversions, have previously been reported in an infant with transient abnormal myelopoiesis (Kempski et al, 1998). Deletions of the distal part of one chromosome 21 including AML1 have been reported to occur in children with constitutional trisomy 21 and acute megakaryocytic leukemia (Kempski et al, 1997).…”
Section: Discussionmentioning
confidence: 98%
“…Among seven cases, two had evolved from a prior myelodysplasia. [15][16][17][18] Point mutations [19][20][21][22] and cryptic chromosome 21 rearrangements associated with deletions of AML1 23,24 have also been reported in myeloid disorders. Collectively, these observations point to possible dosage effects of AML1 in the pathogenesis of leukemia.…”
Section: Introductionmentioning
confidence: 99%
“…It occurs in an estimated 10% of neonates with Down’s syndrome [60]but has been reported in normal newborns who are constitutional mosaics for trisomy 21 [62]and in infants in whom trisomy 21 is present only in the ‘leukaemic’ clone [63, 64]. TMD has also been reported in a phenotypically normal newborn infant with trisomy 18 and 21 and complex intrachromosomal rearrangements of chromosome 21 on bone marrow examination [65]. TMD is usually an incidental finding as the majority of patients are well, although most do have hepatosplenomegaly.…”
Section: Transient Myeloproliferative Disordermentioning
confidence: 99%
“…Tetrasomy 21, t(21;21) and i21 are the most common abnormalities seen [67]. Trisomy 12, 14 and additional +21 has been reported in 1 child [65]. Although such changes may raise the possibility of ‘true’, i.e.…”
Section: Transient Myeloproliferative Disordermentioning
confidence: 99%
See 1 more Smart Citation